Frequency and user satisfaction on using communication technologies to support learning: the case of portuguese higher education - Batista, João (2012)
This paper presents several results from a research project about the use of Communication Technologies to support education in the Portuguese Public Higher Education Institutions. The outline of the project, the Communication Technologies taxonomy adopted and the methodology used are described. The results revealed on this paper respect to students (n = 2207) and to teachers (n = 639), and the characteristics of the sample are summarized. Some results about the frequency of use and the user satisfaction of using Communication Technologies are reported, and the next steps are indicated.